Breeding Quality Indicators of Fleg fix Simmental Bureau Bulls in the Study of Productivity - Khodjaev Ulukhodja Turaboevich; Dosmukhamedova Mukhayo Khusnitdinovna (Genius Journals, 2022)
Genotype and breed characteristics of Maqolada Flekfix simmental zotli bulls were studied. The cows of this breed give less milk compared to the cows of the Holstein breed, but the period of use in the farm is higher.
Keywords: Flexfich purebred cattle; weight; family; growth